Voluntary consumption, digestibility and metabolic balance of steers fed with pseudo-steMON of bananas (Musa acuminata, cv. Cavendish) and energetic supplements]. - Martínez Montoya, Luis (1980)
Tesis (M. Sc) -- CATIE; UCR, Turrialba (Costa Rica), 1980